Long term risk of stroke versus acute coronary events after tia and stroke: a population-based study. - Paul, N; Mehta, Z; Silver, L; Geraghty, O; Rothwell, P (2013)
Some preventive treatments, such as statins and antihypertensive drug classes, differ in their relative effectiveness in preventing stroke versus coronary events. However, guidelines for secondary prevention of stroke are based partly on observations that fatal coronary events on long-term follow-up after TIA and stroke exceed fatal recurrent strokes. However, given the substantial fall in population incidence of coronary events in recent decades, it is uncertain whether this excess coronary risk remains.